Financial Management: A System of Relations for Optimizing Enterprise Finances – a Review - Charli Sitinjak; Anne Johanna; Buschhaus Avinash; Bevoor Bevoor (Yayasan Adra Karima Hubbi, 2023)
Effective financial management is critical to the success of any organization. This review paper provides a comprehensive analysis of financial management as a network of interdependent processes that require coordinated action among investors, creditors, and managers. The paper examines the function of financial management within an organization and its role in achieving financial optimization. Drawing on extensive research, the review paper identifies the four pillars of efficient financial management: planning, budgeting, forecasting, and monitoring. It emphasizes the importance of open communication and coordinated action among all parties involved in financial decisions. By closely monitoring financial performance, financial management can guarantee that an organization is making the most of its available resources. The review paper also stresses the significance of strong leadership in financial management. Effective financial management requires skilled managers who can navigate the complex web of financial relationships within an organization. By analyzing key aspects of financial management, the review paper provides valuable insights into how organizations can optimize their financial management processes.